THE USE OF SMALL GROUP DISCUSSION AS LEARNING INTERACTION TO ACTIVATE THE SECOND YEAR STUDENTS TO SPEAK ENGLISH AT MACHINE DEPARTMENT OF SMK NEGERI 2 PAYAKUMBUH - Sandra Zurina (English Language Education and Current Trends (ELECT), 2022)
This research was aimed to find out wether or not the useof small group discussion could activate the second year students of Machine Department of SMK Negeri 2 Payakumbuh to speak English. This research employed a pre experimental method, and it used one group pre test and post test design. Treatment (X) was given between pre-test (T1) and post-test (T2). The population of this study was the second year students of Machine Department of SMK Negeri 2 Payakumbuh, and the number of sample was 30 students. The instruments used in this study were observation checklist and speaking test. The finding of this study showed the use of small goup discussion could activate the students to speak English. It was indicated by the improvement of activities done by students from meeting to meeting as much as 93.19%. It was also indicated with the fact that the t-test value (10.740) was higher than the t-table value at significant level of 0.05 and degree of freedom n-1 (1.711). In other words, the use of small group discussion technique was able to give greater contributionin teaching and learning speaking. REFERENCES Aleen, D. E. (2001) Mimimizing the Perils of Small Group Discussion. Center for Teaching Excelent. Online (http://www.vcu.edu/cte/resources/nfrg/14_04minizing_peril_of.htm)   Brown, Douglas (1994) Teaching by Principles: An Interactive Approach to Language Pedagogy. London: Prentice Hall International Ltd. Byrne, Donn (1995) Teaching Oral English. Harlow: Longman Group UK Limited. Canal in Richards and Schmidt (2002 Chastain, Kenneth (1976 ) Developing Second Language Skills. Third Edition. New York: McNally College Publishing. Clark, Herbert H. and Eve V. Clark (1977) Psychology and Language: An Introduction to Psycholingustics. San Diego: Kascourt Brace Jovanich. De Boer, John (1987) Basic Language: Message and Meaning. New York: Haper Row Publisher. Drekurs, Rudolf and B. Gunawan (1982) Maintaning Sanity in the Classroom: Management Technique. New York: Haper Collins Publishing. Frederick, E. (1993) A Plan for Small Group Discussion. Online (http://extension.missouri.edu/explore/common/dm0460.htm) Glistrap, Robert L. and Willian R. Martin (1975) Current Strategies for Teachers: A Resoruce for Personalizing Instruction. Santa Monica, California: Goodyear Publishing Company, Inc. Harmer, Jeremy (1998) How to Teach English. New York: Longman. Hatch, Evelyn and Anne Lazaraton (1991) The Research Manual. New York: Newbury House Publisher. Jabu, Baso (2000) Upaya Peningkatan Kemampuan Menyimak Siswa Kelas 1 SMU N2 Makassar melalui Teknik LWS (Listening-Writing-Speaking). Makassar: FBS Universitas Negeri Makassar. McKeachie, W. J.(1999) Teaching Tips: Strategies, Research, and Theory for College and University Teachers. Boston, Massachusetts: Houghton Mifflin Company. Mikundan (2008) Active Speaking. Online (http://www.mikundan.com/portofolio/winstaru/wvcontents/jobaids/aecr/speak.html Muttakin, M. (1992) Activating the Students to Speak English through Pair Tasks in SMU 3 Ujung Pandang. Unpublished Thesis. Ujung Pandang: FPBS IKIP Ujung Pandang. Noni, Nurdin (2003) A Hybrid of Face to Face Teaching and Computer Assisted language Learning in ELT Based on Individual References. Unpublished Dissertation. Makassar: Pastgraduate Program of Hasanuddin University. Nunan, David (1993) Designing Tasks for Communication Classroom. New York: Cambridge University Press. O’driscoll, Nina and Adrian Pilbeam (1987). Meetings and Discussions. London: Longman Group UK Ltd. Rivers, M. W. (1981) Teaching Foreign Langauge Skills. Chicago: University of Michigan Press. Rosma.(2002) Improving Students’ Communicaive Competence through Group Discussion in the Second Year Students of SMUN 2 Maros. Unpublished Thesis. Makassar: FBS Universitas Negeri Makassar. Steven, Runnebohn, M. Jospeh Mazza, and B. Dan Curtis (1979) Communication for Problem Solving. New York: Wiley and Sons, Inc. Publisher. Ur, Penny (1996) A Course in Language Teaching Practice and Theory. Sydney: The Press Syndicate of the University of Cambridge.